Evaluating the financial robustness of special purpose vehicles involved in the delivery of defence private finance initiatives - Ansari, I A (Cranfield University, 2014)
Public sectors in the developed and emerging economies have been witnessing a period of intense change over the past three decades as a result of the development of free-market economy across the globe. In the UK, the public sector in 1970s (that comprised of nationalised industries) was severely criticised for being wasteful, and subject to political intervention, thereby making them inefficient systems for delivering public services. To put matters right, successive governments from the late 1970s embarked on public sector reforms. These reforms centred on increasing the role of private sector in delivering public services. Privatisation, the implementation of accruals-based accounting and application of compulsory competitive tendering in the public sector were some of these reforms. Public-private partnerships, including private finance initiatives (PFIs), introduced in the 1990s, were a continuation of these reforms. In the defence sector, various reforms carried out prior to 1990s failed to completely remove cost and time overruns in defence projects. PFIs were introduced to further rectify the failures of previous reforms in the defence sector because they were purported to provide better value for money. Defence PFIs are long-term agreements whereby the Ministry of Defence, MoD, contracts to purchase quality services on a long-term basis from the private sector (through the special purpose vehicle, SPV) in which the private sector provides all the finance required in constructing the asset that is used to provide the services. Value for money of PFIs is about economy, efficiency and effectiveness. The question, though is whether, Defence PFIs provide value for money as claimed by the MoD? The purpose of this thesis is to evaluate the effectiveness of three categories: 1) accommodation, 2) equipment and 3) training of Defence PFIs by assessing the financial robustness (over a six-year period) of the SPVs engaged in their delivery. This research employs a multi-method methodological approach to gather data. Qualitative research methods were employed in exploring and understanding customer-supplier relationships and included, PPPs, PFIs in general (and Defence PFIs in particular), the public sector reforms that brought about private sector integration, 4 defence reforms, and Defence PFI policies. Quantitative research was used to collect and evaluate financial data on SPVs (used in Defence PFIs). Research analysis provided mixed results regarding the financial robustness of SPVs employed in the delivery of Defence PFIs. The profit margins of SPVs involved in the delivery of Defence PFIs relating to the category of accommodation were the highest. This is followed by SPVs in the category of Defence equipment and then by SPVs in the category of Defence training. Interestingly, the majority of SPVs involved in the delivery of Defence PFIs relating to accommodation have sound financial health. On the other hand, most SPVs relating to the other two categories have serious financial problems and therefore show cause for concern. Based on research findings of this study, a number of important policy recommendations are advanced to raise the effectiveness of PFIs in the defence sector and the wider public sector.
© Cranfield University, 2014
Keywords: Defence procurement; Public-private partnerships; Outsourcing; Public finance intiatives